Clinical trial methodology to assess the efficacy/effectiveness of long-acting antipsychotics: Randomized controlled trials vs naturalistic studies. (January 2017) - Fagiolini, Andrea; Rocca, Paola; De Giorgi, Serafino; Spina, Edoardo; Amodeo, Giovanni; Amore, Mario
Abstract: Schizophrenia presents unique difficulties in clinical trial design associated with the condition's variable presentation and clinical course, and multiple features influencing affect, cognition, volition and perception. Randomized controlled trials (RCTs) are explanatory studies using a carefully selected patient population, predefined assessment intervals and, generally, symptom-focused endpoints. Naturalistic studies are pragmatic, with no active intervention, and outcomes that are generally those used in clinical practice (e.g. hospitalization, relapse rate). Both naturalistic studies and RCTs have pros and cons, making it difficult for physicians in clinical practice to apply research findings to their own treatment decisions. The choice of clinical trial design can have a significant impact on the comparative effectiveness or efficacy of drugs. This is particularly true for studies comparing long-acting injectable (LAI) antipsychotics with oral antipsychotics in schizophrenia, in which RCTs generally show no benefit for LAIs over oral drugs, whereas observational studies do. The more pragmatic the study design, the more likely it is to show a benefit for LAIs versus oral therapy. This article reviews the pros and cons of different study types, using published examples. Criteria are outlined to help physicians design appropriate prospective studies in schizophrenia including the relevant pragmatic and/or explanatory features, as required. Highlights: Assessing the efficacy of antipsychotics drugs in schizophrenic patients is challenging. RCTs give reliable results in a selected population. Naturalistic studies reflect real world clinical practice but are highly biased. Both type of studies are required to gage the true clinical efficacy/effectiveness. Using features from both types of studies can overcome some of their limitations.